1997
DOI: 10.1097/00005392-199703000-00103
|View full text |Cite
|
Sign up to set email alerts
|

Endothelins in Canine Genitourinary Tissues

Abstract: Endothelins are ubiquitous in the canine lower GU tract with predominant localization to the epithelial elements. Endothelins are also functionally active in canine GU tissues, but the specific role of endothelins in the physiology and pathophysiology of GU tissues requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Indeed, the present study demonstrated that both ET A and ET B are present in the epithelial cells of the human urinary bladder. These findings are in line with previous reports that ET A and ET B are expressed along the lower genitourinary tract [34,42,43] . It would be of interest to compare urinary ET receptor excretion between normotensive and hypertensive subjects, an approach that could be of value in exploring the pathophysiology of hypertension and salt sensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, the present study demonstrated that both ET A and ET B are present in the epithelial cells of the human urinary bladder. These findings are in line with previous reports that ET A and ET B are expressed along the lower genitourinary tract [34,42,43] . It would be of interest to compare urinary ET receptor excretion between normotensive and hypertensive subjects, an approach that could be of value in exploring the pathophysiology of hypertension and salt sensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…The present study indicates that, in keeping with previous findings in vivo, expression of the ET-1 gene in vitro is primarily an epithelial phenomenon (5). In contrast, attempts to amplify ET-1 sequences from stromal cell RNA by RT-PCR failed to produce a detectable signal.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in the prostate suggest that ET-1-like immunoreactivity is associated primarily with the glandular epithelium, with ET A and ET B receptors predominating in the stromal and glandular components, respectively (5,10). Previous studies in the prostate suggest that ET-1-like immunoreactivity is associated primarily with the glandular epithelium, with ET A and ET B receptors predominating in the stromal and glandular components, respectively (5,10).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to their effects on vascular smooth muscles, ETs cause contractile responses in the trachea [5][6][7], bronchus [8], and uterus [9], positive inotropic and chronotropic effects on the myocardium [10], and are mitogenic for cultured smooth muscle cells [11][12][13] and fibroblasts [14]. ETs produce prolonged contractile responses in isolated urinary tract smooth muscles from rabbits [15][16][17] and humans [8], and cause rhythmic contractions of the rabbit pelvis [18]. regional distributions of autonomic and calcium antagonist receptors in the urinary tract correlate well with physiological functions [25,26], we investigated the functional (pharmacological) and biochemical properties of ET receptors in the proximal, middle and distal rabbit prostatic urethra.…”
Section: Introductionmentioning
confidence: 99%